Penerapan Metode Kooperatif model STAD dalam Meningkatkan Prestasi Siswa Kelas III Reg C pada Mata Pelajaran Insya' di TMI Al-Amien Prenduan Tahun Ajaran 2022 – 2023 - Akbar Filayati, Ali; Saiful Anam (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to examine the effect of applying the cooperative method of the Student Teams Achievement Division (STAD) model in improving the achievement of class three "C" students in the Insya' (composition) subject at Al-Amien Prenduan Islamic Boarding School for the 2022–2023 academic year.The problem of this research originated from the observation of the students' low ability level in writing Insya' (composition) because teachers still rely on traditional methods such as lectures and individual assignments, which results in low motivation and learning outcomes.The researcher used a qualitative descriptive method with observation, interview, and documentation instruments to collect data. The results showed that the application of the STAD model contributed to increasing student participation levels, developing their ability to work together, and improving test results compared to the previous period.This study also explains that the supporting factors for the success of this model are teacher competence, student enthusiasm, and a conducive learning atmosphere, while the inhibiting factors include the low intelligence of some students and their lack of attention during lessons.